2020
DOI: 10.1002/ldr.3830
|View full text |Cite
|
Sign up to set email alerts
|

Examining the impact of rangeland condition on water conservation by using an integrated modelling approach

Abstract: Rangelands in the arid and semi-arid regions of Iran are under pressure from frequent degradations and extreme climate conditions, which have affected water conservation and delivery of ecosystem services. The timely and efficient assessment of rangeland state/condition impact on water conservation is crucial in rangeland management. This work represents an integrated modelling approach by linking the Soil and Water Assessment Tool (SWAT) and the Integrated Valuation of Ecosystem Services and Tradeoffs (InVEST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Ultimately, farmers' anticipations regarding future seasonal weather serve as a pivotal factor in guiding cropping decisions [65]. In semi-arid regions like the Atrak basin, where grasslands are prevalent, an annual rainfall range of 300-600 mm (mm) may be considered favorable for maintaining healthy grassland coverage, while, generally, for successful dry agriculture, regions may require annual rainfall ranging from 200 to 500 mm, with variations based on specific crop requirements and local conditions [66]. Sustainable management strategies should prioritize measures to mitigate the impact of droughts, enhance soil moisture retention, and improve the resilience of ecosystems and agricultural systems to climate variability.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, farmers' anticipations regarding future seasonal weather serve as a pivotal factor in guiding cropping decisions [65]. In semi-arid regions like the Atrak basin, where grasslands are prevalent, an annual rainfall range of 300-600 mm (mm) may be considered favorable for maintaining healthy grassland coverage, while, generally, for successful dry agriculture, regions may require annual rainfall ranging from 200 to 500 mm, with variations based on specific crop requirements and local conditions [66]. Sustainable management strategies should prioritize measures to mitigate the impact of droughts, enhance soil moisture retention, and improve the resilience of ecosystems and agricultural systems to climate variability.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in the special issue highlight these aspects. For instance, Azimi et al (2021) examine rangeland degradation's impact on water conservation in Iran's Atrak River Basin, revealing a strong link between rangeland condition and water conservation. Shrestha and Acharya (2020) focus on Nepal's Kathmandu Valley, exploring how historical and projected land‐use changes affect ecosystem service values.…”
Section: Land Systems Ecosystem Services and Managementmentioning
confidence: 99%
“…Yang et al (2019) quantitatively assessed water production in the Xiangjiang River Basin and, through sensitivity analysis, showed that precipitation is the most important factor affecting water production. Azimi et al (2020) quantitatively analyzed the impact of runoff on Iranian pastures and determined the impact of different pasture conditions on water conservation functions. Wang et al (2019) quantitatively assessed water production and water conservation in the Shiyang River Basin and analyzed the impact of land use transformation on aquatic ecosystem services.…”
Section: Introductionmentioning
confidence: 99%